Hepatitis B and C status among health care workers in the five main hospitals in eastern Libya - Abdel-Nasser Elzouki; Salwa M. Elgamay; Abdeulaziz Zorgani; Omer Elahmer (Elsevier, 2014)
Summary: The aim of the present study was to determine the frequency of hepatitis B and C transmission to health care workers (HCWs) in five major hospitals in eastern Libya and to analyze how the risk of these infections are affected by the type of occupation, hospital work place and working period. From July 2008 to June 2009, 601 HCWs (mean age: 32.90 ± 8.85 years) were tested for HBV and HCV markers using ELISA techniques. Polymerase chain reaction (PCR) was performed on all positive samples of HBsAg and Anti-HCV antibody to determine the level of HBV-DNA and HCV-RNA viremia, respectively. The overall frequency of HBsAg positivity was 1.8%. Anti-HBc, HBeAg and Anti-HBe antibodies were found in 8.5%, 0.7% and 8.0% of samples, respectively. The HBV-DNA level was positive in 55% of all HBsAg-positive samples. Approximately half of the HCWs (51.4%) were Anti-HBs antibody positive. The overall positivity rate of Anti-HCV antibodies was 2.0%, and HCV-RNA was positive in 33.3% of these samples. Overall, 52% of HCWs reported receiving full vaccination doses (three doses) against HBV infection. Among them, anti-HBs positivity was approximately 98.0%. 3.9% of those who never received any HBV vaccination dose were HBsAg positive, compared to 1.3% HBsAg positive in those HCWs who had received one or two doses of hepatitis B vaccine (p = 0.01 for all comparisons). Nurses and nurse-aides had the highest rates of both HBsAg and Anti-HCV among the studied HCWs (HBsAg: 2.1% and 3.2%; Anti-HCV: 3.2% and 4.9%, respectively). It is noteworthy that doctors also had a relatively high prevalence rate of Anti-HCV (2.2%). Obstetric wards, isolation room, dialysis units and dentist work places had higher frequencies of HBV. HCV was found to be higher in the medical and surgical wards (the prevalence varied between 3% and 5.6%). There was no significant difference between HBsAg status and the work period of HCWs. In conclusion, universal precautions should be applied for the care of all patients by all HCWs. Further, HBV vaccines should be more readily available for Libyan HCWs by reinforcing current vaccination programs. Keywords: Health care workers, Hepatitis B, Hepatitis C, Hepatitis B vaccine, Libya